Mistreatments of Autism Spectrum Disorder - Aswani, Neha (Journal of the Pakistan Medical Association, 2023)
The Editor, Autism Spectrum Disorder (ASD) is an umbrella, constructed to describe difficulties in social communication, with a very confined range of interests and fixed patterns along with atypical sensory-motor behaviors beginning in early childhood. It is estimated that over 350,000 children are on the spectrum in Pakistan, and the prevalence continues to rise(1). Research and studies have shown that early intervention has a positive effect on the later development of children on the spectrum (2). In a child’s life, a sensitive stage of development called the critical period is the time when new connections (synapses) are made that are influenced by environmental stimuli and personal experiences of the child (3). Established diagnosis and intervention in this period influences the brain’s neural plasticity. Hence filling the gap between the child’s growth margin and typically developing peers and supporting their way into adulthood with the competencies necessary to live an independent and carefree life. In underdeveloped nations like Pakistan, there is inadequate knowledge and awareness of ASD. Children are misdiagnosed and caregivers are deluded into the thought of a cure of autism due to the existence of various superstitions and necromantic beliefs(4). Different oil mixtures, herbal medicines, and several other home remedies are practiced: some to elude over-sensitivity or under-sensitivity, some to magically make the child speak etc. However, these practices have no effect, other than losing precious years of the child’s life (5). Parents and caregivers of autistic children should be counseled that ASD is not a disease to cure but a way to adapt. They should be convinced that being autistic is not because some pathogen invaded the brain; rather it is because the brain is wired differently and functions at its own pace. Seminars and webinars should be held for caregivers to help them deal with the psychosocial issues and the social stigma surrounding ASD. There is also a need to create awareness at the government level to better equip people, professionals, and healthcare systems to better cater for the needs of children with ASD. Moreover, efforts should be made to make ASD screening a part of universal pediatric screening so that intervention is provided as early as possible. There is a growing need to understand that ASD is not a curse manifested but an individuality to celebrate.